2011
DOI: 10.1080/ac.66.2.2071252
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding complications with acute coronary syndrome in six Middle Eastern countries

Abstract: Similar to Western studies, bleeding in the setting of ACS is a powerful and independent predictor of poor in-hospital outcomes in patients admitted with ACS in the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Registry data [92], prospective study [93] and randomized controlled trials (RCT) [94] of developed countries in ACS patients reported that the major bleeding risk was between 4.6–10.9%. Compared to developed countries, major bleeding in NCVD was generally low among all ethnic groups (0.2–0.7%) and this finding was similar to those in the ACS Registry in India (0.2–0.3%) (CREATE) and Middle Eastern countries (0.83%) [95]. The finding of a lower risk of major bleeding is intriguing and possibly could be explained by the lower use of invasive cardiac procedures among all ethnic groups as compared to those in developed countries.…”
Section: Discussionsupporting
confidence: 62%
“…Registry data [92], prospective study [93] and randomized controlled trials (RCT) [94] of developed countries in ACS patients reported that the major bleeding risk was between 4.6–10.9%. Compared to developed countries, major bleeding in NCVD was generally low among all ethnic groups (0.2–0.7%) and this finding was similar to those in the ACS Registry in India (0.2–0.3%) (CREATE) and Middle Eastern countries (0.83%) [95]. The finding of a lower risk of major bleeding is intriguing and possibly could be explained by the lower use of invasive cardiac procedures among all ethnic groups as compared to those in developed countries.…”
Section: Discussionsupporting
confidence: 62%